Genome‐wide association study of genetic variants related to anthracycline‐induced cardiotoxicity in early breast cancer. Issue 7 (20th June 2020) - Park, Boram; Sim, Sung Hoon; Lee, Keun Seok; Kim, Hak Jin; Park, In Hae
Abstract: We performed a genome‐wide association study to investigate the association between single nucleotide polymorphisms and anthracycline‐induced cardiotoxicity (ACT) in patients diagnosed with early breast cancer. From January 2000 to December 2015, 8490 patients underwent breast surgery at the National Cancer Center in Korea. Patients who received doxorubicin (cumulative dose 240 mg/m 2 ‐300 mg/m 2 ) with or without trastuzumab as a neoadjuvant/adjuvant therapy were included in our cohort. Sixty‐seven patients in our cohort were diagnosed with ACT. Clinical data, including age, body weight, height, cancer stage, trastuzumab treatment, comorbidities, and concomitant medications, were collected retrospectively. Patients were classified as having either persistent or transient ACT based on their clinical course. In total, 346 946 single nucleotide polymorphisms in 42 cases and 215 controls were tested in this study. Body mass index (BMI) ≥25 kg/m 2 [odds ratio (OR) = 2.45, 95% confidence interval (CI), 1.23‐4.88, P = .011] and trastuzumab use (OR = 2.40, 95% CI, 1.11‐5.17, P = .026) were identified as significant risk factors. We found 7 genetic variants for ACT including rs17530621 ( SHISA3, P = 3.10E−06), rs11894115 ( MPP4, P = 4.71E−06), rs58328254 ( RPL7, P = 6.09E−06), and rs117299725 ( PRUNE2, P = 8.53E−06), although none of these variants reached the Bonferroni‐corrected significance level when adjusted for BMI and trastuzumab use ( = α1.44E−07 based on 0.05/346 946). rs117299725 was a common variant when only the persistent ACT group was analyzed separately. It is meaningful that our study analyzed comprehensively the influence of genetic variation on ACT, along with some clinical factors in Asian breast cancer patients who received anthracycline with or without trastuzumab. Further research will be needed on candidate genetic variants found in this study. Abstract : In this study, we addressed potent genetic variants related with anthracycline induced cardiotoxicity in Korean early breast cancer patients adjusting various clinical factors with a long follow‐up period. The results of our study showed that in anthracycline treatments with a cumulative dose not exceeding 300 mg/m 2, clinical factors were more associated with cardiotoxicity than genetic factors. Several possible genetic variants found in this study may require further study.